Elucidating Antibacterial Activity and Mechanism of Daphnetin against Pseudomonas fluorescens and Shewanella putrefaciens - Wenru Liu; Jun Mei; Jing Xie (Journal of Food Quality, 2020)
In this research, the antibacterial activity and mechanism of daphnetin against Pseudomonas fluorescens and Shewanella putrefaciens were evaluated. The minimum inhibitory concentration (MIC) of daphnetin on P. fluorescens and S. putrefaciens was 0.16 and 0.08 mg·mL−1, respectively. The growth curve test also showed that daphnetin had a good antibacterial effect. The results of intracellular component leakage and cell viability analysis illustrated that daphnetin destroyed the morphology of the cell membrane. According to scanning electron microscope and transmission electron microscope observations, the treated bacterial cells displayed obvious morphological and ultrastructural changes in the cell membrane of the two tested strains, whichconfirmed daphnetin’s damage to the integrity of the cell membrane. The findings indicated that daphnetin mainly exerted its antibacterial effect by destroying the membrane and suggested that it had good potential to be as a natural food preservative.